2016
DOI: 10.1016/j.tjem.2016.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Social media, FOAMed in medical education and knowledge sharing: Local experiences with international perspective

Abstract: Social media, through the Internet and other web-based technologies, have become a means of communication and knowledge-sharing. In this article, we provide details about the social media traffic of various scientific activities, the organizations of which we have played an active role in. We also provide information in our native language through our FOAMed website, which has been published for about 30 months, with us acting as editors. We are comparing these local and limited ventures with examples from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 19 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…Acilci.net , a FOAM blog in Turkish, was reported to have been visited 3,500 times in its first month. 36 St.Emlyn’s blog grew from 3497 to 36,377 average monthly views between 2012–2016. 37 Other reports from the Academic Life in Emergency Medicine blog examined the activity and impact of FOAM for specific topics such as resident well-being, team-based learning, and resident teachers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acilci.net , a FOAM blog in Turkish, was reported to have been visited 3,500 times in its first month. 36 St.Emlyn’s blog grew from 3497 to 36,377 average monthly views between 2012–2016. 37 Other reports from the Academic Life in Emergency Medicine blog examined the activity and impact of FOAM for specific topics such as resident well-being, team-based learning, and resident teachers.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, a FOAM blog publishing in Turkish reported that 10.6% of views were from 111 different countries, possibly doctors from Turkic origins. 36 Similarly, the geographically dispersed access to iEM platforms may be attributed to the users who speak English as a primary or secondary language; however, built-in automatic translation placed on our website may also have facilitated the use of the website for users with little or no English proficiency. 36 Our findings may imply that FOAM platforms in English seem to have considerable international reach, but how publishing in other prevalent or multiple languages might affect the international reach and the distribution of views remains to be discovered in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Looking at individuals, motivational factors behind sharing play a major role and influence the process (Razmerita & Nielsen, 2016;Sirous & Watson-Patridge, 2016). The explicit and tacit knowledge is shared and managed across social media in various frameworks: realtime dispersion of knowledge (Cevik et al, 2016), co-production and sharing of knowledge on trip content communities (Edwards et al, 2017), knowledge sharing in online communities (M. Hajli & M. Hajli, 2013), dispersion of knowledge on Twitter (Xu et al, 2015), or enterprise social media and knowledge sharing practices (Rode, 2016). Some authors are skeptical and believe that social media limits knowledge sharing (Gibbs & Eisenberg, 2013).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The content captures different knowledge on a topic observed and presented on social media. Social media has become a significant, affordable and reliable communication channel with strong potential for sharing explicit and tacit knowledge online (Cevik, Akoglu, Eroglu, Dogan, & Altunci, 2016). Generally, social media provides immense capabilities for knowledge dislocation in a virtual environment and is suitable for both individuals and knowledge workers to facilitate knowledge flows (Rode, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These interactive databases have created a dynamic online community and a family of FOAM users worldwide [9]. Since FOAM leans towards self-directed problem-based learning, various medical schools across the world have also embedded it into their curriculum [10-12].…”
Section: Introductionmentioning
confidence: 99%